Corporate Governance and Firm Performance: A Study of Sri Lankan Manufacturing Companies - Velnampy, T. (My University, 2013)
Corporate governance is about putting in place the structure, processes and mechanism that ensure that the firm is being directed and managed in a way that enhances long term share holder value through accountability of managers and enhancing organizational performance. Corporate governance refers to a set of rules and incentives by which the management of a company is directed and controlled. Hence good corporate governance maximizes the profitability and long term value of the firm for shareholders. There is a great awareness among the researchers to carry out the researches in “corporate governance’. Very little researches on “corporate governance” are available in Sri Lanka and need to be empowered companies to pay a special attention on corporate governance. In a way, the present study is initiated on “corporate governance and firm performance” with the samples of 28 manufacturing companies using the data representing the periods of 2007 – 2011. Board structure, board committee, board meeting and board size including executive directors, independent non-executive directors, and non executive directors were used as the determinants of corporate governance whereas return on equity (ROE) and return on assets (ROA) were used as the measures of firm performance. The study found that determinants of corporate governance are not correlated to the performance measures of the organization. Regression model showed that corporate governance don’t affect companies’ ROE and ROA. Further recommendations are also put forwarded in the research.
Keywords: Corporate governance; firm performance; board size; board structure; board committee; board meeting